KAJIAN EKSPERIMENTAL TERHADAP KONDUKTIVITAS DAN DIFUSIVITAS TERMAL BUAH SEMANGKA - Johanes, Susanto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
In the tropics, when the fruit is going to be cropped, the fruit temperature is same as the ambient temperature. It could reach more than 40 degree Celcius. One of the methods to make the fruit not easily damaged at the post-harvest is by applying the pre-cooling method. It aims to retard the respiration, minimize the vulnerability from the attack of micro-organisms, reduce the loss of water, and reduce the cooling load on the carrier and also the storage system. The fruit thermal conductivity and diffusivity values become the first important data to be recognized in order to determine the precooling time pro-cess to the desired temperature.The research is aimed to recognize the watermelon thermal conductivity and diffusivity values. Modeled as a ball shaped object, the water-melon is chilled in the cooler by natural convection. In the cooling process, the changing temperature in its fruit was recorded in the computer by using IC LM 35 sensors, every 5 minutes. The sensor was set in the ambient, on the fruit surface and in it’s inside with five different radius. There were three of watermelon by weight as 2,590 kg, 3,925 kg and 5,195 kg had been observed.In this research, the calculation of the watermelon thermal conductivity and diffusivity was based on the thermal resistance and capacity formulation. By numerical method, the average value of watermelon thermal conductivity was calcu-lated as 0,438 W/moC. Meanwhile the average value of thermal diffusivity was calculated as 1,137x10-7 m2/s.